Discursive transformations of stateness in the written press - Fatala, Norma (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2009)
This article approaches the discursive constructions of the nation State and citizenship in the written press from a socio-semiotic perspective.  It studies the written press in Córdoba, Argentina, over the course of the week in which Néstor Kirchner takes power in Argentina (23to 30 May, 2003). It is argued that the very nature of the written material produced over this period, including all the written press and local papers, regardless their own reading contract, generate some kind of construction of the nation State and the Political community which, in spite of any attempts to be objective, is heralds the establishment of a new institution.